\(\left(x^2+y\right)\left(x+y^2\right)=\left(x-y\right)^3\)
\(\Leftrightarrow x^3+\left(xy\right)^2+xy+y^3=x^3-xy\left(x-y\right)+y^3\)
\(\Leftrightarrow xy\left(xy+1\right)=xy\left(y-x\right)\)
Xét hai TH:
+ TH1: xy = 0: Khi đó \(\left[{}\begin{matrix}x=0\\y=0\end{matrix}\right.\).
+ TH2: xy \(\ne\) 0: Ta được xy + 1 = y - x
\(\Leftrightarrow xy+x-y+1=0\)
\(\Leftrightarrow x\left(y+1\right)-y-1+2=0\)
\(\Leftrightarrow\left(x-1\right)\left(y+1\right)=-2\). Ở đây dễ rồi
a) ta có : \(x^2+x+6=y^2\) \(\Leftrightarrow\left(x+\dfrac{1}{2}\right)^2=y^2-\dfrac{23}{4}\ge0\)
\(\Leftrightarrow\left[{}\begin{matrix}y\ge\dfrac{\sqrt{23}}{2}\\y\le\dfrac{-\sqrt{23}}{2}\end{matrix}\right.\) \(\Rightarrow\) \(y=???\) thế vào tìm x
b) tương tự
c) \(x^3-y^3=3xy+1\Leftrightarrow x^3-1=y^3+3xy\)
\(\Leftrightarrow\left(x-1\right)\left(x^2+x+1\right)=y\left(y^2+3x\right)\)
\(\Leftrightarrow x-1\) và \(y\left(y^2+3x\right)\) cùng dấu \(\Rightarrow\) ...
d) ai gỏi lm giùm nha